Screen Adaptation of the Film Love Never Comes on Time: Narrative Changes from Puthut EA to Hanung Bramantyo's Cinema - Uvina Binafi’atil Ilmi; Fina Zaidatul Istiqomah (UIN Raden Mas Said Surakarta, Indonesia, 2026)
This study examines the screen adaptation of the novel Cinta Tak Pernah Tepat Waktu by Puthut EA into its film version directed by Hanung Bramantyo, focusing on narrative transformations across literary and cinematic media. The study is important because the shift from written text to audiovisual form often changes narrative structure and meaning, yet such transformations remain insufficiently explored in contemporary Indonesian literary adaptations. The novel was selected as the research object due to its introspective narration, psychological conflicts, and subjective treatment of time, which pose significant challenges for visual representation. The research draws on adaptation theory, narratology, and multimodal discourse analysis. Using a descriptive qualitative approach, it applies qualitative content analysis. Narrative units from the novel and film scenes were collected through close reading and documentation and analyzed comparatively using an extralingual matching method. The findings identify 15 narrative transformations categorized into reduction, addition, and variation, indicating that the film creatively reconstructs the story’s meaning according to cinematic logic. Penelitian ini mengkaji proses ekranisasi novel Cinta Tak Pernah Tepat Waktu karya Puthut EA ke dalam film adaptasi sutradara Hanung Bramantyo dengan fokus pada transformasi naratif antarwahana sastra dan sinema. Kajian ini penting karena adaptasi dari teks tulis ke audiovisual sering menimbulkan perubahan struktur dan makna cerita yang belum banyak dianalisis dalam konteks sastra Indonesia kontemporer. Novel ini dipilih sebagai objek karena dominasi narasi introspektif, konflik psikologis, dan pengolahan waktu subjektif yang menghadirkan tantangan ketika divisualisasikan ke medium film. Penelitian berlandaskan teori adaptasi, naratologi, dan analisis wacana multimodal. Metode yang digunakan ialah pendekatan kualitatif deskriptif dengan analisis isi. Data berupa unit naratif novel dan adegan film dikumpulkan melalui teknik simak. Hasil menunjukkan 15 transformasi naratif yang meliputi penciutan, penambahan, dan variasi. Film merekonstruksi makna cerita secara kreatif sesuai logika sinema.